Usos dos verbos ser e estar no português brasileiro: uma abordagem funcional - Santos, Ana Lúcia dos (2016)
variation of uses of ser and estar verbs by brazilian speakers. It presupposes that the systemic units of a language acquire new functions when they are used in interpersonal relationships. The problem arises from the different functions acquired by these verbs that are not covered by systemic grammar rules of the portuguese language. The main goal of this paper is contribute with brazilian portuguese gramatical studies, and the specific goals are: 1. Describing the use of ser and estar verbs in the lexical dimension; 2. Verifying the uses of ser and estar verbs in the propositional dimension; 3. Finding the distinct functions updated in the pragmatic-discursive dimension, on resemantization and grammaticalization in the use of these verbs. The background of this research is that systemic and traditional grammar descriptions are not able to explain the variations of ser and estar in the brazilian portuguese actual use. This research is founded on moderate current of linguistic functionalism, according to Givón (1993), to whom language structure is not separated from its function. The adopted methodological procedure is qualitative, and the corpus was collected in both, writing and oral brazilian speakers uses. The analyses were carried out from the three dimensions proposed by Givón (1993) – lexical, propositional and pragmatic-discursive. The results indicate that, in the lexical dimension, the choice between ser or estar made in the vocabular content complies with lexical system; in the propositional dimension, these verbs partake of personal or impersonal sentences, as lexical verbs or by giving these sentences the notions of spatial location, companion, time, mode, equanimity, possession or quality; in the propositional dimension, duo to communicative purposes of language users, these verbs are grammaticalizated, becoming copula and auxiliary verbs, and ressemantizated, i. e., they acquire new meanings and functions that differ from those from vocabular content. It means that it is impossible to refer to pragmatic-discursive dimension without considering propositional and lexical dimensions. This research opens up new prospects of ser and estar studies given the variety of uses of these verbs